Assessment of the effectiveness of artificial intelligence-based oral screening solution in the diagnosis of dental calculus, stains, and dental caries (Logy AI oral screening solution) - R., Pradeep Kumar; Tiwari, Nivedita; Panchbhai, Anand; Chellappa, Lalitha R.; Suresh, Sushanthi; Pandiyan, Indumathy (International Journal of Advances in Medicine, 2024)
Background: The objective of this study was to clinically evaluate the precision of Logy AI’s oral screening solution. This innovative module, driven by artificial intelligence, operates seamlessly through WhatsApp and as a standalone smartphone application. It is designed to detect various dental issues such as stains, calculus, and caries, utilizing images captured by a smartphone camera. The accuracy of the module was assessed by comparing its diagnoses with those made by dental professionals. Methods: A prospective clinical study was conducted in Saveetha Dental College, a tertiary care hospital in the southern part of India with 325 patients. Smartphone images taken were sent to the Logy AI oral screening solution which predicted if the patient had any oral hygiene issues like stains, calculus, and caries. Patients were examined by a dentist with visual-tactile and orthopantomogram (OPG) examination and were documented. Both were compared. Results: The accuracy of the Logy AI oral screening solution for the detection of stains, calculus, and caries was comparable with the dentist’s diagnosis. The accuracy was 85% for caries, 97% for stains, and 83% for calculus. The sensitivity was 88% for caries, 89% for stains, and 82% for calculus. Conclusions: The Logy AI oral screening module demonstrates potential as an efficient oral screening tool suitable for community-level deployment, particularly in remote regions lacking access to costly dental equipment and healthcare professionals. Its accuracy and efficiency make it well-suited for operation in low-resource settings. Moreover, it holds promise as a valuable home screening tool for individuals seeking to monitor their oral health proactively.